TRANSFORMING SHARIA BUSINESS COMMUNICATION IN THE DIGITAL AGE: NAVIGATING BETWEEN TECHNOLOGICAL ADVANCEMENT AND ETHICAL RESPONSIBILITY - Muhammad Arisman; Muhamad Husen Ihsanudin (UIN Sunan Gunung Djati Bandung, 2025)
This study investigates the transformation of Sharia-compliant business communication in the digital age, analyzing how technological advancements both challenge and support ethical practices in Islamic economic activities. Using a literature review method, the paper explores patterns, dilemmas, and adaptive strategies for maintaining Sharia values in digital interactions, particularly in the context of e-commerce, financial technology, and social media. Key ethical principles such as ṣidq (honesty), amānah (trust), and ‘adl (justice) are examined alongside real-world digital practices. The study reveals that while digital tools increase efficiency and outreach, they also pose risks such as clickbait, data misuse, and unethical marketing. As a solution, the research proposes adaptive strategies based on maqāṣid al-sharī‘ah, collaborative regulatory frameworks, and ethical digital literacy for Sharia businesses. This paper contributes to the development of a value-driven framework for ethical communication in Islamic business, balancing modern innovation with timeless Islamic ethics.